The effect of dietary total antioxidant capacity of individuals with type 2 diabetes on metabolic and oxidative parameters: A cross-sectional study: Dietary antioxidant capacity in type 2 diabetes - Özpak Akkuş, Özlem; Mermer, Meltem; Gen, Ramazan; Çimen, Mehmet Burak Yavuz; Koutelidakis, Antonios; Dönmez, İhsan (Journal of Surgery and Medicine, 2026)
Background/Aim: The aim of this study is to determine the dietary total antioxidant capacity (DTAC) values and levels of certain serum oxidative parameters in individuals with previously and newly diagnosed type 2 diabetes and to evaluate the impact of these findings on glycemic values and metabolic parameters. Methods: This study was conducted with a total of 97 participants aged 19-64, comprising 35 individuals with a previous type 2 diabetes diagnosis, 32 individuals with a recent type 2 diabetes diagnosis, and 30 healthy participants. During face-to-face interviews, participants provided descriptive information, physical activity levels, and anthropometric measurements. DTAC was calculated from three-day dietary intake records using various methods. Serum samples were collected for the analysis of glycemic, lipid, and oxidative parameters. Results: The results show that DTAC values (specifically derived from total radical-trapping antioxidant potential (TRAP) and total phenolics (TP) values)) and serum TAC levels tend to decrease with both prolonged diabetes age and when compared to individuals without diabetes (P<0.05). DTAC values were found to have a significant effect on some oxidative parameters like TAC, paraoxonase 1, and arylesterase (P<0.05), while serum oxidative parameters were found to have no significant effect on glycemic and lipid parameters. Conclusion: It was concluded that low DTAC may be a risk factor related to oxidative stress depending on type 2 diabetes and diabetes age.